Preliminary Assessment of Utilizing Treated Arabica Coffee Waste as Adsorbent Material for Heavy Metals Removal from Aqueous Solution - Siti Koriah Zakaria, Pao Ter Teo, Siti Nor Alya, Abdul Hafidz Yusoff (International Journal of Advanced Science and Technology, 2019)
In this study, treated coffee waste was used to remove heavy metals (Cd, Cr and Pb) from synthetic water. For the adsorption studies, operational parameters such as adsorbent dosage and contact time were studied. For the characterization, Fourier-transform infrared spectroscopy (FT-IR) and Scanning electron microscope (SEM) were used to identify functional group and observed the surface of treated coffee waste. Removal of heavy metals were studied using 100 ml of synthetic water contained 7.5 ppm (Pb), 4.8 ppm (Cr) and 0.9 ppm (Cd) at room temperature. All adsorption processes were carried out for different dosage and contact time to identify the optimum condition for adsorption. Concentrations of synthetic water were measured using atomic adsorption spectroscopy (AAS). The results were analysed using removal percentage of heavy metals and adsorption capacity. The highest removal percentage for 0.5g of adsorbent content were 74.4 % (Pb), 50% (Cr) and 44% (Cd) respectively. For 0.7 g, the removal percentage was Pb (84%) followed by Cd (35%) and Cr (30%). For 1 g and 3 g, the removal percentage were Pb (85%), Cd (40%), Cr (-33%) and 75.5 % (Pb), 50.5 % (Cd) and 20% (Cr) Every dosage was observed with different contact time of 30 minutes, 1 hour and 2 hours. The best contact time for 0.5 g, 0.7 g, 1 g, and 3 of dosage was 1 hour to reach equilibrium state. In conclusion, this study indicates that treated coffee waste could be employed as a potential adsorbent for heavy metals removal from synthetic water and could perform better than untreated coffee waste.